2015
DOI: 10.1002/anie.201504254
|View full text |Cite
|
Sign up to set email alerts
|

Silver‐Catalyzed Cross‐Coupling of Isocyanides and Active Methylene Compounds by a Radical Process

Abstract: Isocyanides are versatile building blocks, and have been extensively exploited in C-H functionalization reactions. However, transition-metal-catalyzed direct C-H functionalization reactions with isocyanides suffer from over-insertion of isocyanides. Reported herein is a radical coupling/isomerization strategy for the cross-coupling of isocyanides with active methylene compounds through silver-catalysis. The method solves the over-insertion issue and affords a variety of otherwise difficult to synthesize β-amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 85 publications
(36 citation statements)
references
References 74 publications
1
35
0
Order By: Relevance
“…Thec ross-coupling reaction between 1a and 2-tosylacetonitrile (2n)w as completely suppressed by the addition of the radical inhibitor 2,2,6,6-etramethylpiperidine-N-oxyl (TEMPO) or 2,6-di-tertbutyl-hydroxytoluene (BHT), [23] thereby suggesting that the reaction goes through af ree radical intermediate [Eq. [32] Scheme 3. However we could not isolate adducts of the scavengers formed from radical intermediates.Deuterium-labeling studies using [D]-2n unambiguously confirmed the active methylene compounds as the source of the hydrogen atom in the product [Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Thec ross-coupling reaction between 1a and 2-tosylacetonitrile (2n)w as completely suppressed by the addition of the radical inhibitor 2,2,6,6-etramethylpiperidine-N-oxyl (TEMPO) or 2,6-di-tertbutyl-hydroxytoluene (BHT), [23] thereby suggesting that the reaction goes through af ree radical intermediate [Eq. [32] Scheme 3. However we could not isolate adducts of the scavengers formed from radical intermediates.Deuterium-labeling studies using [D]-2n unambiguously confirmed the active methylene compounds as the source of the hydrogen atom in the product [Eq.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, isocyanides have reactivities similar to multicomponent reactions, and they are often used for C-H functionalization reactions. In 2015, the Bi group reported a silver-catalyzed cross coupling of isocyanides 72 and active methylene compounds 73 to access various β-aminoenones 74 and tricarbonylmethanes 75 by a radical process (Scheme 43) [61]. To determine the reaction mechanism, both isotope-labeling studies and control experiments with radical scavengers were performed, and the reaction did not proceed in the presence of radical scavengers.…”
Section: Decarboxylative Functionalization and Carboxylationsmentioning
confidence: 99%
“…However, all of these reactions were carried out with silver reagents. While silver is also a common transition metal catalyst for C-H functionalization [26][27][28][29][30][31][32], silver-mediated alkoxylation of aryl C(sp 2 )-H bonds will be attractive but challenging.…”
Section: Introductionmentioning
confidence: 99%